Seeing Colleagues as Learning Resources: The Influence of Mathematics Teacher Meetings on Advice-Seeking Social Networks. (April 2020) - Horn, Ilana; Garner, Brette; Chen, I-Chien; Frank, Kenneth A.
Teacher collaboration is often assumed to support school's ongoing improvement, but it is unclear how formal learning opportunities in teacher workgroups shape informal ones. In this mixed methods study, we examined 77 teacher collaborative meetings from 24 schools representing 116 teacher pairs. We coupled qualitative analysis of the learning opportunities in formal meetings with quantitative analysis of teachers' advice-seeking ties in informal social networks. We found that teachers' coparticipation in learning-rich, high-depth meetings strongly predicted the formation of new advice-seeking ties. What is more, these new informal ties were linked to growth in teachers' expertise, pointing to added value of teachers' participation in high-depth teacher collaboration.